Subframization and stabilization for superintuitionistic logics. (17th January 2019) - Bezhanishvili, Guram; Bezhanishvili, Nick; Ilin, Julia
Abstract: With each superintuitionistic logic (si-logic for short), we associate its downward and upward subframizations and characterize them by means of Zakharyaschev's canonical formulas, as well as by embedding si-logics into the extensions of the propositional lax logic $PLL$ . In an analogous fashion, with each si-logic, we associate its downward and upward stabilizations and characterize them by means of stable canonical formulas, as well as by embedding si-logics into extensions of the intuitionistic $S4$ .